Senior secondary school students' risk of disengagement from further education, employment or training - Cavanagh, Rob; Reynolds, Peter (AARE, 2007)
In Western Australia, the school leaving age was mandated to rise from 15 Years to 16 Years in 2007. This policy has resulted in a large number of students remaining at school and entering the senior years of schooling. Of interest in this study were the students who would not normally have remained at school, particularly those who may have disengaged from schooling. Data were obtained from school and education district office student services staff on 23 attributes of 5313 Year Ten students identified at risk of not completing schooling, future training or entering employment. The data were dichotomous and the multi-variate nature of these data rendered it unsuitable for Rasch Model analysis but amenable to interpretation using Binomial Logistic Regression. Two models were tested with each containing a different dependent variable and common independent variables. The dependent variables for the respective models were: Model 1 - Student Risk of Disengagement; and Model 2 - Student Severe Risk of Disengagement. The study identified particular student attributes perceived by school and district office student services staff that statistically predicted two levels of disengagement with schooling, future training or future employment.